2020
DOI: 10.1108/ijefm-01-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

The application of enduring involvement theory in the development of a success model for a craft beer and food festival

Abstract: PurposeThe purpose of this research paper is to examine whether enduring involvement theory plays a role in predicting craft beer and food festival visitors' experience of the festivalscape. Though craft beer and brewing is a growing area of research, there has been limited studies and theory application in this area. Around the world, craft breweries are increasing in number and producing more unique styles of beer as the demand for craft beer increases. Craft beer consumers visit many of these breweries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
2
24
2
Order By: Relevance
“…The development of new recipes and the use of social media have been the most common types of innovation (Alonso et al , 2018). Beckman et al (2020) explain how CB festivals promote craft brewing in some regions.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The development of new recipes and the use of social media have been the most common types of innovation (Alonso et al , 2018). Beckman et al (2020) explain how CB festivals promote craft brewing in some regions.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Some element of gamification could be used to increase engagement; for example voting for “people's favourites” in the animal Shows, home-participation in cookery classes and quizzes or educational “treasure-hunts” could all increase interaction and promote learning about different features of rural life. However, we accept that the recreation of the full sensory experiences of tastes, smells sounds and social interaction described by the festivalscape literature (Beckman et al , 2020) cannot be fully recreated in an online Show. Enhanced visitor interactivity at online Shows combining home-based activities with online participation and conversation is essential for their future development and wider community-building.…”
Section: Discussion: Creating and Conceptualising An E-eventscape–stakeholders And Value Generationmentioning
confidence: 99%
“…An eventscape can be viewed as a construct combining the tangible elements of an event with the experiences provided (Tattersall and Cooper, 2014; Carneiro et al , 2019). The festivalscape literature further emphasises the atmosphere created at the event (Mason and Paggiaro, 2012; Beckman et al , 2020), but the complexity of the experiences that form a visitors sensation of the atmosphere are much more difficult to recreate online.…”
Section: E-servicescapes and Eventscapes: Towards A New Model Of The E-eventscapementioning
confidence: 99%
“…The craft beer tourists are motivated by various elements featured in the festival such as food, facilities, and entertainment. At the festival, tourists have the opportunity to taste craft beers from multiple breweries in one stop [23]. In turn, the brewers can explain product details directly to the consumers, which leads to the promotion of sales.…”
Section: Literature Review 21 Craft Beer Scene and Craft Beer Tourism In Thailandmentioning
confidence: 99%
“…In the case of the TBF, the craft beer entrepreneurs constitute one of the salient elements that attracted attendants to the festival. As festivals are events that bring brewers and craft beer brands together, it allows attendants to have close communication with these entrepreneurs [23]. Evidence from an online source showed that one Instagram account posted several images of herself with various brewers at TBF.…”
Section: A Proposed Fifth Domain Of Tourism Experiencementioning
confidence: 99%